2021
DOI: 10.1021/acsanm.0c03364
|View full text |Cite
|
Sign up to set email alerts
|

Large Perpendicular Magnetic Anisotropy in Nanometer-Thick Epitaxial Graphene/Co/Heavy Metal Heterostructures for Spin–Orbitronics Devices

Abstract: Nanometer-thick epitaxial Co films intercalated between graphene (Gr) and a heavy metal (HM) substrate are promising systems for the development of spin–orbitronic devices due to their large perpendicular magnetic anisotropy (PMA). A combination of theoretical modeling and experiments reveals the origin of the PMA and explains its behavior as a function of the Co thickness. High quality epitaxial Gr/Co n /HM­(111) (HM = Pt,Ir) heterostructures are grown by intercalation below graphene, which acts as a surfacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 63 publications
4
40
0
Order By: Relevance
“…In the present work we show that this regime is reached at Co 3 thickness and that the DMI contributions of the stacking defects cancel out. Interestingly, this DMI behaviour contrasts with that of the magnetocrystalline anisotropy of f ct Gr/Co n /Pt(111), where a complex behaviour with Co n thickness is found that depends on the competition between the contributions from the f ct bulk (in-plane) and twin boundary defects (out-of-plane) [35].…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…In the present work we show that this regime is reached at Co 3 thickness and that the DMI contributions of the stacking defects cancel out. Interestingly, this DMI behaviour contrasts with that of the magnetocrystalline anisotropy of f ct Gr/Co n /Pt(111), where a complex behaviour with Co n thickness is found that depends on the competition between the contributions from the f ct bulk (in-plane) and twin boundary defects (out-of-plane) [35].…”
Section: Introductionmentioning
confidence: 74%
“…Our interface-resolved DFT study of DMI in Gr/Co n /Pt(111) heterostructures with varying Co layer thickness shows that the regime of additivity of interfacial DMI is reached already at n = 3 atomic planes and also that the D-vectors have an almost negligible outof-plane component. As the perpendicular magnetocrystalline anisotropy prevails at much larger n values [35], a sizable DMI interaction to have spin canting and chiral exchange effects are expected to be robust. However, unlike the magnetocrystalline anisotropy itself, interfacial DMI is insensitive to the internal structure of the Co layer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations